2013 IEEE International Symposium on Circuits and Systems (ISCAS2013) 2013
DOI: 10.1109/iscas.2013.6572251
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic analysis on ring oscillator-based true random number generators

Abstract: Security of implementation of ciphers in hardware has already been well studied, nevertheless ciphers are not the only hardware block used for cryptography. True random number generators (TRNGs) are also significant cryptography blocks since they are used to provide secret keys, random protection masks, initial values to other security blocks such as ciphers. The security of TRNG implementations is thus of paramount importance. Recently, electromagnetic channel has been used to efficiently attack ring oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 5 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…We can also conclude that the activity of the AES block inside the FPGA has no influence on the result of the electromagnetic differential frequency analysis. More information on the method itself and more results can be found in [18].…”
Section: Results Of Our Differential Frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We can also conclude that the activity of the AES block inside the FPGA has no influence on the result of the electromagnetic differential frequency analysis. More information on the method itself and more results can be found in [18].…”
Section: Results Of Our Differential Frequency Analysismentioning
confidence: 99%
“…13 The simulation results (Figs. 18,19) showed that the two models produced exactly the same results. We obtained the same effect as in Figs.…”
Section: Electrical Simulationmentioning
confidence: 92%
“…Indeed, it is a suitable PUF for both in terms of feasibility, cost and efficiency. However, the RO-PUF has security problems since it can be cloned [22] and is subject to locking phenomena [24].…”
Section: The Tero-puf For Iotmentioning
confidence: 99%
“…Indeed, the locking phenomena correspond to the manipulation of the frequency of oscillating cell in order to force them to operate at a particular frequency. More explanation of this can be found in [22]. Since the principle of the RO-PUF is based on the frequency mismatch of theoretically identical cells, lock them to the same frequency becomes a real issue.…”
Section: The Tero-puf For Iotmentioning
confidence: 99%
See 1 more Smart Citation